Analysis of disease activity and response to treatment in a large Spanish cohort of patients with systemic lupus erythematosus. (June 2015) - Pego-Reigosa, J M; Rúa-Figueroa, Í; López-Longo, F J; Galindo-Izquierdo, M; Calvo-Alén, J; Olivé-Marqués, A; del Campo, V; García-Yébenes, M J; Loza-Santamaría, E; Blanco, R; Melero-González, R; Vela-Casasempere, P; et al.
Objectives: The objectives of this paper are to study the impact of disease activity in a large cohort of patients with systemic lupus erythematosus (SLE) and estimate the rate of response to therapies. Methods: We conducted a nationwide, retrospective, multicenter, cross-sectional cohort study of 3658 SLE patients. Data on demographics, disease characteristics: activity (SELENA-SLEDAI), damage, severity, hospitalizations and therapies were collected. Factors associated with refractory disease were identified by logistic regression. Results: A total of 3658 patients (90% female; median SLE duration (interquartile range): 10.4 years (5.3–17.1)) were included. At the time of their last evaluation, 14.7% of the patients had moderate-severe SLE (SELENA-SLEDAI score ≥6). There were 1954 (53.4%) patients who were hospitalized for activity at least once over the course of the disease. At some stage, 84.6% and 78.8% of the patients received glucocorticoids and antimalarials, respectively, and 51.3% of the patients received at least one immunosuppressant. Owing to either toxicity or ineffectiveness, cyclophosphamide was withdrawn in 21.5% of the cases, mycophenolate mofetil in 24.9%, azathioprine in 40.2% and methotrexate in 46.8%. At some stage, 7.3% of the patients received at least one biologic. A total of 898 (24.5%) patients had refractory SLE at some stage. Renal, neuropsychiatric, vasculitic, hematological and musculoskeletal involvement, a younger age at diagnosis and male gender were associated with refractory disease. Conclusions: A significant percentage of patients have moderately-to-severely active SLE at some stage. Disease activity has a big impact in terms of need for treatment and cause of hospitalization. The effectiveness of the standard therapies for reducing disease activity is clearly insufficient. Some clinical features are associated with refractory SLE.